Rhabdomyolysis and Acute Kidney Injury in a Patient with Severe Form of Covid-19 Pneumonia- A Case Report - Canevska Taneska, Aleksandra; Trajcheska, Lada; Milenkova, Mimoza; Kuzmanovski, Nikola; Ristovska, Vesna; Rambabova Bushljetic, Irena; Dokikj, Dejan; Naumovski, Krume; Spasovski, Goce (Balkan Cities Association of Nephrology, Dialysis, Transplantation and Artificial Organs, 2020)
Introduction. The ongoing pandemic with the novel Corona virus poses unprecented challenges for the me- dical professionals worldwide. Acute kidney injury is frequently seen in patients infected with corona virus and often associated with a poor patient outcome. Rhabdo- myolysis has been recognized as one of the possible contributing mechanisms. Case. A 68-year-old man was referred to the emergen- cy department complaining of a dry cough, myalgia, general weakness with devastated energy feeling, chest pain and difficulties in breathing, symptoms he expe- rienced in the past five days. He also noticed that his urine was dark and in reduced amount. Quick antigen test for SARS CoV2 was performed, and the patient found Covid-19 positive. He was admitted at the hos- pital ward in a covid-designated unit. Laboratory findings revealed elevation of the inflammatory markers and elec- trolyte disbalance. Metabolic degradation products were markedly increased, serum urea was 44mmol/L (RF=2.7- 7.8 mmol/L) and serum creatinine 689umol/L (RF=45- 109umol/L), when deterioration of the kidney function was diagnosed. Urgent intermittent hemodialysis treatment was initiated. Patient suffered from a severe form of covid-19 pneumonia and was continuously on high flow oxygen mask. Duration of the patient hospitalization was 30 days, and thereafter, he was transferred to the reha- bilitation center for 28 days. Complete restoration of the physical motion and activity was accomplished, oxygen support was no longer needed, since he main- tained blood oxygen saturation above 95%. Renal func- tion has also been recovered with degradation products maintained within normal ranges. Conclusion. Rhabdomyolysis in covid-19 patients should be always kept in mind. Sometimes it can be an initial clinical manifestation in covid-19 patients [15], but on the other hand it can be presented as a late complication sometimes caused by the therapy itself. Multidiscipli- nary and comprehensive approach in the diagnosis, treat- ment and follow up of the patients can only guarantee timely detection and wide range of therapeutical moda- lity, leading to a better prognosis and outcome.
Keywords: covid-19 infection; acute kidney injury; rhabdomyolysis; renal replacement therapy